Introduction of english to early childhood through the direct method - Sundari; Harmanto, Bambang; Rahmawati, Ida Yeni (Al-Athfaal: Jurnal Ilmiah Pendidikan Anak Usia Dini, 2025)
Background : The reality of English learning at the PAUD level is still faced with various challenges, such as the lack of available learning media, the lack of teachers with adequate qualifications, and the limited variety of teaching methods. Aim : This study aims to determine, explain, and analyze the implementation of English introduction to early childhood through the Direct Method at Pembina Ponorogo State Kindergarten. Method : This study uses a qualitative approach with observation, interview, and documentation methods. The subjects of the study included 24 children, consisting of 8 boys and 16 girls, teachers, and principals. The research indicators include 4 aspects of language skills including listening, speaking, reading, and writing. Result : The results of the study revealed that the Implementation of the Direct Method at Pembina Ponorogo Research findings indicate that the application of the Direct Method is not only effective in stimulating children's cognitive and linguistic abilities but also integrates fine motor stimulation—making it more holistic than other conventional approaches. Compared to other media or methods, the Direct Method offers an intuitive and interactive learning framework based on the stimulus-response principle, which is highly suited to the learning characteristics of young children. Conclusion : The strength of this method lies in the active role of the teacher as both a facilitator and a language model, thereby bridging theory and practice in a practical way. Although challenges such as maintaining children's focus still exist, this method has proven to significantly enhance listening, speaking, reading, and writing skills. Therefore, kindergarten/preschool teachers are advised to optimize the integration of fine motor activities, provide consistent guidance, and create a supportive learning environment to maximize the potential of this method.